IMPROVEMENT OF STUDENT LEARNING ACTIVITY AND LEARNING OUTCOMES BY USING PROBLEM-BASED LEARNING MODEL ON HUMAN REPRODUCTIVE SYSTEM TOPIC IN GRADE XI IPA 4 AT SMAN 2 SOPOSURUNG BALIGE - Ruben ES Siregar; Binari Manurung (Universitas Negeri Medan, 2016)
This study’s purpose was to improve or increase the student learning activity and learning outcomesbu using Problem-based Learning model on human reproductive system topic. This research type wasclassroom action research due to two cycles that used. The objects were students class XI IPA 4 in SMAN 2Soposrung Balige. The data got by using multiple-choice question to measure the students learning outcomesand an instrument to observe the students learning activities. The result showed that the application ofproblem-based learning model can increase learning activities of students from the first cycle to second cycle of23.06%. The application of problem-based learning model can improve student learning outcomes in submaterial human reproductive system was indicated by an increase learning outcomes of the first cycle tosecond cycle of 19.8%. Then, the data that displayed good progress of learning mastery of student hasincreased from first cycle to the second cycle about 53.4%.Keywords: Problem-based Learning, Student Learning Activity, Student Learning Outcomes, HumanReproductive System